MODEL OF INTRA-DEPARTMENT MANAGEMENT OF MOTIVATION OF TEACHERS OF HIGHER EDUCATION - Elena Gennadievna Gutsu; Yuliya Yurievna Chilipenok (Высшее образование в России)
In the context of reforming higher education, the problem of developing and implementing a new, effective management policy aimed at attracting, retaining and motivating highly qualified scientific and pedagogical personnel is of particular relevance. However, as noted in a number of studies, university teachers find themselves in a difficult situation, which is caused by a decline in public recognition of the value of the profession, staff shortages, turnover and aging of staff, a crisis of motivation and professional identity in higher education amid significant complications in professional activities. The current stage of development of higher education is characterized by large-scale innovation processes, therefore, the management of the motivation of teachers of higher education institutions should be considered as the management of motivation in the context of innovation. The basis of this approach is the orientation on creativity and stimulation of innovative behavior of personnel. It is obvious that the task of managing the motivation of the work of teachers of higher education should be solved as soon as possible, without interrupting the professional activities and within the working teams themselves. The article presents the experience of developing and testing a layered model of intra-departmental management of university teachers' motivation, which is based on the idea of forming a motivated team and creating a corporate culture that will help effectively manage innovative processes at the university.